EFFICIENT SOLUTION OF LARGE MOMENTS PROBLEMS: WIRE GRID MODELING CRITERIA AND CONVERSION TO SURFACE CURRENTS - Ferguson, Thomas R. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A banded matrix iterative solution method for linear simultaneous equations arising from thin wire moments problems has been applied to a variety of problems of intermediate electrical size with the number of unknowns ranging up to 1000. Using a convergence criterion of 1 percent, solution efficiencies varied from 2.5 for short, fat objects up to 35 for long, thin objects. Application of the method requires some expertise. Approximate guidelines for wire grid modeling of surfaces have been developed for the moments formalism used. A new method for computing surface currents from grid currents is discussed. [Vol. 3, No. 1, pp. 55-81 (1988)]